What are Production Determinants of Bioeconomy? - Maciejczak, Mariusz (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The concept of bioeconomy focuses on clustering different socio-economic processes of both traditional and innovative sectors of economy that focus on the use of renewable resources, and by applying knowledge and innovative technologies, and delivering products and services that are important from private and public points of view. Such an approach requires utilization of resources that differ from classical economic classification of production factors. The paper argues that instead of land, labor, capital and entrepreneurship, from the bioeconomy point of view it is more important to look at: renewable resources such as biomass sources, investments in research and development activities and people engaged in such activities as well as innovations, which could be considered as production determinants. Based on the latest Eurostat data for the year 2011, the paper presents the state of these determinants in the European Union’s main bioeconomy sectors.